2006
DOI: 10.1080/08990220600741119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact location on vibrotactile thresholds at the fingertip

Abstract: Vibrotactile thresholds depend on the characteristics of the vibration, the location of contact with the skin, and the geometry of the contact with the skin. This experimental study investigated vibrotactile thresholds (from 8 to 250 Hz) at five locations on the distal phalanx of the finger with two contactors: (i) a 1-mm diameter circular probe (0.78-mm(2) area) with a 1-mm gap to a fixed circular surround (i.e., 7.1-mm(2) excitation area), and (ii) a 6-mm diameter circular probe (28-mm(2) area) with a 2-mm g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
(22 reference statements)
3
17
0
2
Order By: Relevance
“…It seems probable that, within each frequency, the same channel mediated thresholds with both the small and the large contactor, since thresholds obtained with both contactors were correlated at all frequencies (Table 4) except at 16 Hz. The pattern of correlations, both between frequencies, and between contactors, as well as the spatial summation only occurring at high frequencies, implies that thresholds at high frequencies (63, 125 and 250 Hz) were determined by the Pacinian channel with both contactors and that thresholds at lower frequencies (8, 16 and 31.5) were determined by non-Pacinian channels with both contactors, consistent with Whitehouse et al (2006).…”
Section: Fingertipsupporting
confidence: 64%
“…It seems probable that, within each frequency, the same channel mediated thresholds with both the small and the large contactor, since thresholds obtained with both contactors were correlated at all frequencies (Table 4) except at 16 Hz. The pattern of correlations, both between frequencies, and between contactors, as well as the spatial summation only occurring at high frequencies, implies that thresholds at high frequencies (63, 125 and 250 Hz) were determined by the Pacinian channel with both contactors and that thresholds at lower frequencies (8, 16 and 31.5) were determined by non-Pacinian channels with both contactors, consistent with Whitehouse et al (2006).…”
Section: Fingertipsupporting
confidence: 64%
“…At the fingertip, 160-Hz thresholds increased as the probe diameter reduced from 10 to 1 mm, consistent with mediation by the Pacinian channel [7,8,9]. There was a significant difference between thresholds obtained with 1-mm and 3-mm probes, unlike the thenar eminence, because at the fingertip the Pacinian channel is most sensitive even with a 1-mm probe [7].…”
Section: Spatial Summationsupporting
confidence: 50%
“…With 300-Hz vibration, thresholds reduced with a slope of 3 dB per doubling of contactor area between 0.025 and 0.10 cm 2 (probes with diameters of 1.8 and 3.6 mm), but not between 0.38 and 0.75 cm 2 (probes with diameters of 7 and 10 mm). Whitehouse et al [8] studied vibrotactile thresholds at the fingertip with excitation areas of 0.071 and 0.79 cm 2 , and observed lower thresholds with larger excitation areas at 63, 125 and 250 Hz, but not at 8, 16 and 31.5 Hz. Morioka et al [9] obtained vibrotactile thresholds at the fingertip with excitation areas of 0.071 cm 2 (1-mm diameter probe) and 0.79 cm 2 (6-mm diameter probe) and found that thresholds at 63, 125 and 250 Hz, where thresholds were believed to be determined by the Pacinian channel, were on average 10.2 dB lower with the larger probe.…”
Section: Introductionmentioning
confidence: 99%
“…The VPT curve is also significantly influenced by the size of the probe. For a probe 1 mm in diameter, the VPT values were lower at the stimulus frequencies of 8 and 16 Hz and higher at frequencies of above 125 Hz in comparison with the values obtained using a 6-mm probe 14) . The mean VPT values obtained with a P8 pallesthesiometer in this study are higher at the frequencies of 4 Hz, 25 Hz, 31.5 Hz and 125 Hz in comparison with the VPTs contained in Annex A of the ISO 13091-2 15) .…”
Section: Discussionmentioning
confidence: 89%